1981
DOI: 10.1017/s0317167100042992
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Porphyric Neuropathy: A Preliminary Report

Abstract: SUMMARY:An experimental model for the study of porphyric neuropathy is presented. Injection of either tetraphenylporphinesulfonate (TPPS), hematoporphyrin derivative (HpD), or delta-aminolevulinic acid (ALA) into mice resulted in markedly decreased motor nerve conduction velocity (MNCV). The MNCV returned to normal within one week following the injection of large doses of A LA, and within three weeks following the injection of close to lethal doses of HpD. hut there was no recovery of nerve function within 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 34 publications
(24 reference statements)
3
26
0
Order By: Relevance
“…Chemical porphyria, although generally used as an experimental model for understanding the porphyria disease states, has now been suggested as a novel means of endogenous sensitisation for PDT (Divaris et al, 1990). This approach involves the administration of 5-aminolaevulinic acid (ALA) which results in endogenous photosensitisation both in cultured cells (Malik & Djaldetti, 1979) and in whole animals (Sima et al, 1981). ALA is present naturally in mammalian cells since it is the first committed intermediate in the haem biosynthesis pathway.…”
mentioning
confidence: 99%
“…Chemical porphyria, although generally used as an experimental model for understanding the porphyria disease states, has now been suggested as a novel means of endogenous sensitisation for PDT (Divaris et al, 1990). This approach involves the administration of 5-aminolaevulinic acid (ALA) which results in endogenous photosensitisation both in cultured cells (Malik & Djaldetti, 1979) and in whole animals (Sima et al, 1981). ALA is present naturally in mammalian cells since it is the first committed intermediate in the haem biosynthesis pathway.…”
mentioning
confidence: 99%
“…In this biosynthetic pathway, the rate limiting step is that involved in the synthesis of ALA which is controlled by a regulatory feedback inhibition (Marriott, 1968;Rimington, 1966). By administering a large quantity of exogenous ALA both to in vitro systems as well as whole animals, it has been shown that the natural regulatory mechanism can become overloaded and as a result, porphyrin intermediates of the biosynthetic pathway, particularly protoporphyrin IX (PPIX), accumulate (Malik & Djaldetti, 1979;Sima et al, 1981). PPIX is a potent photosensitiser.…”
mentioning
confidence: 99%
“…Malignant tissues usually developed much stronger fluorescence than did the adjacent normal tissues. We found that (contrary to dogma) the porphyrins in at least some of the fluorescing tissues were being synthesized in situ rather than in the liver or hemopoietic organs (23). These observations formed the basis for our subsequent studies in experimental animals, cancer patients, and human volunteers (24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Endogenous Porphyrins As Tissue Photosensitizersmentioning
confidence: 79%